Stand Up and Shout Out: Women’s Fight for Equal Pay, Equal Rights, and Equal Opportunities in Sports - Steidinger, Joan (Rowman & Littlefield Publishers, 2020)
Today, women have greater opportunities to participate in sport than ever before, particularly due to the passage of Title IX in 1972. Yet, despite all this growth, women still struggle to hold leadership positions, become coaches of both girls and boys teams, receive equal pay, and get even adequate coverage in the media. In Stand Up and Shout Out: Women's Fight for Equality in Sports, Joan Steidinger explores the three crucial areas in sport that remain huge concerns for women: leadership, money, and media. Steidinger looks at the number of ways in which women experience vast inequalities by examining topics such as the politics of sport, sexual assault, the #MeToo movement, pay equity, women in coaching positions, and the experiences of women of color and LGBTQ athletes. Interviews with leading authorities in the field and prominent female athletes are interwoven throughout to add both expert and personal perspectives to the conversation. Stand Up and Shout Out does more than justinform readers about these important issues; its purpose is to create enlightened discussions around the unequal treatment of women and present readers with “action steps” so we can all become active contributors toward improving this situation. This is an ideal time to fight for women’s equality in sport, as it draws attention to the growing need for advocacy for girls and women around the world in all areas of life.